Siddhāntalakṣaṇam - Gaṅgeśa ca. 13. Jh. (Rāṣṭrīyasaṃskṛtavidyāpīṭhagranthamālā, 2011)
Work dealing with the definition of vyapti (regular concommitance of the major and middle terms) in neo-Nyaya philosophy; includes three classical commentaries